2008
DOI: 10.1002/cssc.200800039
|View full text |Cite
|
Sign up to set email alerts
|

Toward Environmentally Benign Oxidations: Bulk Mixed Mo‐V‐(Te‐Nb)‐O M1 Phase Catalysts for the Selective Ammoxidation of Propane

Abstract: Selective oxidation catalysis is of vital importance to society, being used to provide about a quarter of all organic chemicals and intermediates used to make consumer goods and the industrial products that rely on them, [1] and is key to many proposed green chemical processes targeted to cut back harmful emissions.[2] As we look to the future, selective oxidation catalysis increasingly holds the promise of eliminating or at least dramatically curbing pollution from chemical and refining processes by employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Each cluster was separated from its neighboring images by *11 Å of vacuum in the x, y, and z directions. In the bulk M1 phase, the V and Mo cations are terminated by oxo groups on opposite sides of the bulk ab planes [6,17], but the nature of the surface ab plane termination by oxo groups remains a subject of on-going research [29]. In this study, V and Te were capped by oxygen forming vanadyl (V=O) and telluryl (Te=O) moieties, while the Mo=O groups were present on the opposite side of the cluster.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Each cluster was separated from its neighboring images by *11 Å of vacuum in the x, y, and z directions. In the bulk M1 phase, the V and Mo cations are terminated by oxo groups on opposite sides of the bulk ab planes [6,17], but the nature of the surface ab plane termination by oxo groups remains a subject of on-going research [29]. In this study, V and Te were capped by oxygen forming vanadyl (V=O) and telluryl (Te=O) moieties, while the Mo=O groups were present on the opposite side of the cluster.…”
Section: Methodsmentioning
confidence: 98%
“…Its basal ab plane exhibits 13 crystallographically distinct metal lattice sites (S1-S13) [6]. The 11 lattice sites include 10 octahedral Mo and V sites (S1-S8, S10, S11) and 1 pentagonal bipyramidal Nb site (S9), while the remaining 2 sites are occupied by Te=O species intercalated into hexagonal (S12) and heptagonal (S13) channels [17]. Recent studies of the M1 phase combining high resolution TEM (transmission electron microscopy), synchrotron X-ray, and powder neutron diffraction methods have shown that V, Mo, and Te are present in the 4?/5?, 5?/6?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed active center is outlined by dashed lines the x, y, and z directions. In the bulk M1 phase, the V and Mo cations are capped by oxo groups on opposite sides of the bulk ab planes [1,9], whereas the nature of the surface ab plane termination by oxo groups remains a subject of on-going research [11]. The eight equatorial oxygen atoms in each truncated ab plane were terminated with hydrogen atoms and both the O and H atoms were fixed at a bond length of 0.96 Å during geometry optimization, while all of the other atoms in the cluster models and all the atoms in the adsorbates were allowed to relaxed.…”
Section: Cluster Modelsmentioning
confidence: 99%
“…Direct propane ammoxidation to acrylonitrile catalyzed by the bulk mixed metal oxides has gained considerable attention in recent years [1][2][3] because it is an environmentally benign and potentially more economical process that relies on the abundant propane feedstock than the current process of propene ammoxidation. Among all mixed metal oxides, the bulk mixed Mo-V-Te-Nb-O system is particularly promising because of its significant activity and selectivity in converting propane to acrylonitrile [4] compared to other Mo-V-O based catalysts.…”
Section: Introductionmentioning
confidence: 99%